2013
DOI: 10.1371/journal.pone.0076253
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Protective Rickettsia prowazekii Antigen Recognized by CD8+ T Cells, RP884, Using an In Vivo Screening Platform

Abstract: Rickettsia prowazekii has been tested for biological warfare due to the high mortality that it produces after aerosol transmission of very low numbers of rickettsiae. Epidemic typhus, the infection caused by these obligately intracellular bacteria, continues to be a threat because it is difficult to diagnose due to initial non-specific symptoms and the lack of commercial diagnostic tests that are sensitive and specific during the initial clinical presentation. A vaccine to prevent epidemic typhus would constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 38 publications
(40 reference statements)
1
33
0
1
Order By: Relevance
“…Rickettsial proteins were further analyzed using RANKPEP (http://imed.med.ucm.es/Tools/rankpep.html), which combines MHC class-I-binding affinity and proteasome processing [19]. We used RANKPEP to evaluate the likelihood of peptides predicted by NetMHCpan, IEBD-ANN and SYFPEITHI to be generated via proteasome-processing as we previously described [12]. Analysis of similarity to human and mouse proteins, as well as HLA class-I binding, were performed using Vaxign and Vaxitope, respectively; these programs are available through the Vaccine Investigation and Online Information Network (VIOLIN, http://www.violinet.org/) [20].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rickettsial proteins were further analyzed using RANKPEP (http://imed.med.ucm.es/Tools/rankpep.html), which combines MHC class-I-binding affinity and proteasome processing [19]. We used RANKPEP to evaluate the likelihood of peptides predicted by NetMHCpan, IEBD-ANN and SYFPEITHI to be generated via proteasome-processing as we previously described [12]. Analysis of similarity to human and mouse proteins, as well as HLA class-I binding, were performed using Vaxign and Vaxitope, respectively; these programs are available through the Vaccine Investigation and Online Information Network (VIOLIN, http://www.violinet.org/) [20].…”
Section: Methodsmentioning
confidence: 99%
“…C3H/HeN mice were housed in an animal biosafety level-3 (ABSL3). For immunization, we followed a short immunization protocol that enhances CD8 + T cell responses [21] as we did in our previous report [12]. Generation of antigen presenting (APCs) cell lines expressing rickettsial proteins is described in the supplementary methods section.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A novel vaccine discovery strategy involving nucleofection of antigen-presenting cells targeting the MHC class I pathway with clones expressing R. prowazekii genes was used to immunize mice [15]. Rickettsial challenge with an ordinarily lethal dose of R. typhi revealed that R. prowazekii gene RP884 stimulated cross protection reducing the bacterial load in liver.…”
Section: Rickettsiaceaementioning
confidence: 99%